Performance Analysis of Wireless Sensor Networks. (2015) - Sándor, Hunor; Haller, Piroska; Gál, Zoltán
Abstract: This work focuses on the performance analysis of parallel bidirectional periodic peer-to-peer communication using IEEE 802.15.4 communication. The IEEE 802.15.4 communication standard forms the basis of popular communication protocols for wireless mesh networks such as the ZigBee specification, which received remarkable attention in recent years because of the growing popularity of the Internet of Things. The high rate bidirectional periodic data transfer is a commonly used traffic type in many applications on these networks, such as closed-loop networked control, sensor monitoring, and audio or video transmission. A distributed approach based on the packets received was used to monitor the performance indicators (jitter and packet loss rate) of the peer-to-peer communication in every communication node. As a performance analysis we carried out practical measurements in different cases: with and without ACK; different packet size and period; with and without parallel competitive traffic. Based on the practical results we proposed a parallel data transmission technique that increases the throughput of the sensor network.